2014
DOI: 10.1111/ejss.12132
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene ‐ Holocene palaeosols in the north of Sonora, Mexico: chronostratigraphy, pedogenesis and implications for environmental history

Abstract: Summary Red palaeosols of the late Pleistocene‐early Holocene, both buried and non‐buried, were studied recently in Sonora (NW Mexico) to reconstruct their pedogenesis as well as the palaeoenvironmental conditions. The alluvial palaeosol‐sedimentary sequence of the La Playa archaeological site is a key locality for the buried San Rafael palaeosol, which exhibits a 2Ah‐2Bw‐2BCk‐3Bgk profile and was defined as a Chromic Cambisol. Radiocarbon dates from pedogenic carbonates and charcoal set the soil formation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…The percentage of clay in the Boquillas soil is high (2A 13.3 %, 3A 6.4 %, 6AC 23.7 %, 8AC 65.1 %, and 10AC 26.7 %), and was inherited from the parent material, including micro-aggregates of soils originated at the upland Q3b unit that eroded down into the alluvial plain. In addition, previous studies showed that the predominant clays in soils are smectites, although illites and kaolinites were also identified (Cruz-y-Cruz et al, 2014). It is interesting to observe the increase in the content of illites in the horizons A and AC, with respect to that of the C horizons, which has been interpreted in a preliminary way as a process of illitization of smectites promoted by the semi-arid climate (Retallack, 2001).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The percentage of clay in the Boquillas soil is high (2A 13.3 %, 3A 6.4 %, 6AC 23.7 %, 8AC 65.1 %, and 10AC 26.7 %), and was inherited from the parent material, including micro-aggregates of soils originated at the upland Q3b unit that eroded down into the alluvial plain. In addition, previous studies showed that the predominant clays in soils are smectites, although illites and kaolinites were also identified (Cruz-y-Cruz et al, 2014). It is interesting to observe the increase in the content of illites in the horizons A and AC, with respect to that of the C horizons, which has been interpreted in a preliminary way as a process of illitization of smectites promoted by the semi-arid climate (Retallack, 2001).…”
Section: Discussionmentioning
confidence: 79%
“…The analytic results from the Hornos 2 and Canal 2 profiles present more or less similar soils features, including darker brown-gray color, silty texture, pedogenic structure, subangular blocks, pores, and roots. The 3A horizon from Hornos 2 was dated by 14C with organic soils at 4090-3880 cal BP, and Boletín de la Sociedad Geológica Mexicana / 2019 / 533 DISCUSSION 2C horizon from Canal 2 was dated by 14C with carbonates at 2368-2475 cal BP (Cruz-y-Cruz et al, 2014). We can conclude that the soil formation in both profiles is the result of the same soil development that took place during the late Holocene at the site area, which constitute a Pedological Unit referred to as the BOP.…”
Section: Pedogenic Process and Environmental Formation Of Bopmentioning
confidence: 99%
“…Finally, Cruz‐y‐Cruz et al () investigated red palaeosols of the late Pleistocene‐early Holocene, both buried and non‐buried, in Sonora (NW Mexico) to reconstruct their pedogenesis as well as palaeoenvironmental conditions. The authors suggested that pedogenesis of the San Rafael palaeosol took place under a slightly more humid climate and relative geomorphic stability.…”
Section: Palaeosolsmentioning
confidence: 99%
“…This Special Section comprises a selection of papers showing new and original results in different types of palaeopedological archives, including recent palaeo‐environmental reconstructions carried out in southern (Scarciglia et al , ; Zucca et al , ) and eastern Europe (Łanczont et al , ) and Mexico (Cruz‐y‐Cruz et al , ), as well as novel research on soils developed in urban, industrial and mining materials (Huot et al , ; Jangorzo et al , ).…”
mentioning
confidence: 99%
“…En el noroeste de México, particularmente en el estado de Sonora, los registros paleoambientales holocénicos son limitados, a pesar de la importancia que tiene este periodo para el establecimiento de las condiciones desérticas (Van Devender, 1990;Holmgren et al, 2003). Gran parte de la información generada proviene de estudios palinológicos (Anderson y Van Devender, 1995;Ortega-Rosas et al, 2008), paleopedológicos (Cruz y Cruz et al, 2014;Ibarra-Arzave et al, 2018) y sedimentológicos (Copeland et al, 2012;Schott, 2017). Es por ello que en el presente trabajo se muestran resultados novedosos sobre una secuencia de sedimentos fluviales con paleosuelos intercalados, localizada en el arroyo Tinajas, Sonora, formada en el Pleistoceno terminal-Holoceno, desde una perspectiva geopedológica que permite, de forma integral, proponer una reconstrucción paleoambiental de la región durante el periodo referido.…”
Section: Introductionunclassified